Exploring EFL Teachers’ Teaching Styles at a Junior Secondary School - Nurindah Fadillah Arif; Nurdin Noni; Chairil Anwar Korompot (ARRUS Journal of Social Sciences and Humanities, 2024)
The study aimed to find out the teachers’ teaching styles applied at SMP Telkom Makassar, students’ perceptions, and the teachers’ obstacles faced during teaching. This study was categorized as qualitative research, and the data was collected through observation, TSI questionnaire, and interview. There were six participants in this study, consisting of three teachers, and three students. The findings of this research showed that: (1) Teachers respectively applied various teaching styles in teaching English in the classroom and no one teacher applied only one style in teaching, they applied as a facilitator, delegator, formal authority, personal, expert, academic style, audiolingual, communicative style, and task-based learning style. The dominant teaching styles applied by the participants are facilitator and delegator styles. (2) The students’ perceptions, they feel comfortable learning English with their teachers because their teachers applied various styles to teach not only focusing on the book, but their teachers providing the material using interesting PPT, audio-video conversation, ice-breaking, and games to make their class fun. Another activity that the students enjoyed learning English like discussion with pairs or groups and the atmosphere that is built by the teachers such as interaction with other students, never judging, and yelling at students when they make a mistake. (3) The obstacle that the participants faced during teaching they were exhausted from teaching in large classes that consisted of many students with different characteristics and abilities. Sometimes, they are confused about the method or strategy, and media that are suitable for their students that can increase their ability in English.